1997
DOI: 10.1016/s0042-6989(96)00274-x
|View full text |Cite
|
Sign up to set email alerts
|

Disparity modulation sensitivity for narrow-band-filtered stereograms

Abstract: Stereo thresholds for 84% correct detection of sinusoidal disparity corrugations depicted by narrow-band-filtered random dot stereograms were determined for surfaces as a function of (i) luminance center spatial frequency and (ii) disparity modulation frequency. In addition, supra-threshold depth matching functions for two amplitudes of peak-to-trough depth were determined using similar stimuli. Disparity thresholds followed a U-shaped function when plotted against luminance centre spatial frequency from 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
4
12
2
Order By: Relevance
“…A rotation of this amount would displace a point on the edges of the target by approximately 22.0 arc sec, and create an inter-ocular disparity of 44.0 arc sec (0.7 arc min). This gure is very close to that reported previously for the threshold for cyclopean depth corrugations close to the optimum spatial frequency (Tyler, 1974) and the asymptotic threshold over time for both crossed and uncrossed disparities (Beverley and Regan, 1974a, b) although they are somewhat higher than recent estimates of disparity detection at the optimum point on the disparity sensitivity function, possibly due the effects of probability summation across space (Lee and Rogers, 1997;Bradshaw and Rogers, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…A rotation of this amount would displace a point on the edges of the target by approximately 22.0 arc sec, and create an inter-ocular disparity of 44.0 arc sec (0.7 arc min). This gure is very close to that reported previously for the threshold for cyclopean depth corrugations close to the optimum spatial frequency (Tyler, 1974) and the asymptotic threshold over time for both crossed and uncrossed disparities (Beverley and Regan, 1974a, b) although they are somewhat higher than recent estimates of disparity detection at the optimum point on the disparity sensitivity function, possibly due the effects of probability summation across space (Lee and Rogers, 1997;Bradshaw and Rogers, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…The use of the log domain is motivated by previous work [Didyk et al 2011] and leads to better results. The range of disparity detection thresholds specified by our model is in good agreement with the data in [Lee and Rogers 1997] for measured mid-range disparity and luminance frequencies. For more extreme ranges, similar to [Hess et al 1999], we observe that, for low-frequency disparity corrugations, a wide range of luminance frequencies lead to good stereoacuity, while for higher-frequency disparity corrugations stereoacuity is weak for low luminance frequencies.…”
Section: Threshold Functionsupporting
confidence: 83%
“…We consider suprathreshold luminance contrast, more complex disparity patterns, and explore, how band-tuned luminance contrast interacts with corrugated depth stimuli at various spatial frequencies. Lee et al [1997] measured the impact of luminance frequency on disparity perception for band-pass-filtered random-dot stereograms. They showed that the relationship between disparity sensitivity and luminance frequency exhibits a band-pass characteristic with the maximum located at a luminance frequency of 4 cpd, which is shifted for lower-frequency disparity modulation below 0.25 cpd to around 3 cpd.…”
Section: Introductionmentioning
confidence: 99%
“…Above a disparity corrugation spatial frequency of 1 c/d, the optimum carrier spatial frequency is approximately 2.6x the corrugation spatial frequency. These results resolve what at first appeared to be a discrepancy between the results of a number of previous studies [2], [3], [4]. The consequence of this finding is that in order to validly compare how disparity sensitivity varies as a function of disparity corrugation, spatial frequency measurements should be done under conditions of comparable, and ideally optimal, conditions.…”
Section: Introductionsupporting
confidence: 72%